(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the article, new methods and principles of improving the budgeting of enterprises operating in the Republic of Uzbekistan are considered. Key words: enterprise, management, economic growth, improvement, economic stability.